Recovery from opioid use on a neuropsychoanalytic service - Meadon, Ross; Zhang-James, Yanli; Aslam, Sunny; Johnson, Brian (Frontiers in Psychiatry, 2024)
Abstract Background Little is known about recovery from opioid use disorder (OUD) or outcomes of detoxification and drug-free treatment of chronic opioid therapy (COT). Harm reduction with medications for opioid use disorder (MOUD) is regarded as the only legitimate treatment. Methods The Institutional Review Board (IRB) approved reporting deidentified outcomes. Patients seen over a 10-year period whose records suggested recovery were called and interviewed. Results Overall, 69/86 (80%) confirmed that they had been sober for at least a year, including 41 patients with OUD (75%) and 28 COT patients (90%). 91% were drug-free and 9% were on MOUD. 79% preferred a psychotherapy approach. 21% preferred MOUD. Coming for more treatment and abstinence from tobacco were significantly correlated with recovery. Conclusions This is the first report that we are aware of regarding the frequency of recovery from OUD and COT. We have complicated the discussion about what is the best treatment for patients with OUD and patients on COT. Advising that maintenance is the only legitimate treatment for patients who suffer from OUD or who are on COT seems both premature and jeopardizes the ability of treaters to individualize treatment recommendations.